Statistical analysis of the eSTREAM competition winners - Mohamed Eljadi, Fardous; Alshaikhli, Imad Fakhri Taha (The Institute of Electrical and Electronics Engineers, Inc., 2016)
eSTREAM is a project that was developed over a period of several years. It had the objective of activating the research area of analysis and design of stream ciphers. At the end of this project, seven stream ciphers were selected as the winners. These ciphers were subjected to rigorous cryptanalysis and have resulted in the enhancement of overall understanding of stream cipher design. In previous researches, the randomness properties of these ciphers have been tested but not compared. The purpose of this paper is to compare and analyze the randomness properties of the seven winners of eSTREAM project. NIST test suite is applied to the output sequences. The results show that HC-128 and Trivium comparatively outperform the other ciphers in several tests.